"Values That Vanish into Thin Air": Nurses' Experience of Ethical Values in Their Daily Work. (19th August 2013) - Bentzen, Gro; Harsvik, Anita; Brinchmann, Berit Støre
Abstract : The objective of this study was to examine how nurses experience ethical values as they are expressed in daily practice in a Norwegian hospital. A growing focus in Western healthcare on effectiveness, production, and retrenchment has an influence on professional nursing standards and nursing values. Lack of resources and subsequent ethically difficult prioritizations imply a strain on nurses. This study is qualitative. Data collection was carried out by conducting 4 focus group interviews. The data was analyzed using content analysis. The results are presented in two main themes: (1) values and reflection are important for the nurses; (2) time pressure and nursing frustrations in daily work. The results demonstrate that nurses believe the ethical values to be of crucial importance for the quality of nursing; however, the ethical values are often repressed in daily practice. This results in feeling of frustration, fatigue, and guilty conscience for the nurses. There is a need for changes in the system which could contribute to the development of a caring culture that would take care of both patients and nurses. In an endeavour to reach this goal, one could apply caritative leadership theory, which is grounded on the caritas motive, human love, and mercy.